The relationship between perceived restorativeness and place attachment for hikers at Jeju Gotjawal Provincial Park in South Korea: the moderating effect of environmental sensitivity - Yoon, Jee In; Lim, Soyoun; Kim, Mi-Lyang; Joo, Jinyoung (Frontiers in Psychology, 2023)
Objectives: Jeju Gotjawal Provincial Park provides visitors with opportunities for outdoor recreation and informs visitors of the environmental significance of the park’s ecosystem. This study attempted to examine how the perceived restorativeness of park visitors influenced their place attachment. In addition, the moderating effect of environmental sensitivity on the hypothesized relationship was explored. Methods: Using the purposive sampling method, 408 surveys were collected at Jeju Gotjawal Provincial Park. The hypotheses were tested by confirmatory factor analysis, path analysis, and invariance tests using Lisrel 8.70. Results: The results indicated that perceived restorativeness had a positive influence on place attachment (place identity and place dependence). Further, the hypothesized relationship was stronger for the visitors with higher environmental sensitivity, compared to those with weaker environmental sensitivity. Conclusions: Park managers should consider ways to increase the perceived restorativeness of visitors as they experience the natural environment at the park. Also, since environmental sensitivity played an important role in shaping the perceived restorativeness–place attachment relationship, there is a need for educational programs that can inform visitors of the significance of the natural environment to increase their affection for nature.